An Integrated Systematic Analysis and the Clinical Significance of Hepcidin in Common Malignancies of the Male Genitourinary System - Wang, Xiaogang; Shi, Qianqian; Gong, Pengfeng; Zhou, Cuixing; Cao, Yunjie (Frontiers in Genetics, 2022)
Tumors of the male genitourinary system are of great concern to the health of men worldwide. Although emerging experiment-based evidence indicates an association between hepcidin and such cancers, an integrated analysis is still lacking. For this reason, in this study, we determined the underlying oncogenic functions of hepcidin in common male genitourinary system tumors, including bladder urothelial carcinoma (BLCA), kidney chromophobe (KICH), kidney renal clear cell carcinoma (KIRC), kidney renal papillary cell carcinoma (KIRP), prostate adenocarcinoma (PRAD) and testicular germ cell tumors (TGCT) according to the data from TCGA (The Cancer Genome Atlas). We found that hepcidin was highly expressed in kidney and testicular cancers. Meanwhile, the expression level of hepcidin was distinctly associated with the prognosis and immune cell infiltration in male patients with certain genitourinary system cancers, especially in KIRC. Elevated hepcidin levels also present as a risk factor in male genitourinary system tumors. Moreover, enrichment analyses revealed that some of the principal associated signaling pathways involving hepcidin and its related genes are identified as tumorigenesis-related. Immunofluorescence staining confirmed the conclusion of our immune infiltration analysis in KIRC tissue. In this study, for the first time, we provided evidence for the oncogenic function of hepcidin in different types of male genitourinary system tumors.